1986
DOI: 10.1039/f19868203535
|View full text |Cite
|
Sign up to set email alerts
|

The dielectric properties of zeolites in variable temperature and humidity

Abstract: Measurements are reported of the dielectric response of Na-X, Na-Y and Ca-A zeolites in the frequency range 10 mHz to 10 kHz for a range of humidities and also over a range of temperatures. The extended frequency range compared with earlier studies has enabled a more detailed understanding to be obtained of the low-frequency behaviour, which is dominated by a strongly dispersive dependence on frequency of both the real and the imaginary components of the complex capacitance and has shown the complete absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 1 publication
2
31
0
Order By: Relevance
“…The previous experiments to assess ε of interfacial water mostly relied on broadband dielectric spectroscopy applied to large-scale naturally-occurring systems such as nanoporous crystals, zeolite powders and dispersions 4,5,10,18,19 . These systems allow sufficient amount of interfacial water for carrying out capacitance measurements but the involved complex geometries require adjustable parameters and extensive modelling, which result in large and poorly controlled experimental uncertainties.…”
mentioning
confidence: 99%
“…The previous experiments to assess ε of interfacial water mostly relied on broadband dielectric spectroscopy applied to large-scale naturally-occurring systems such as nanoporous crystals, zeolite powders and dispersions 4,5,10,18,19 . These systems allow sufficient amount of interfacial water for carrying out capacitance measurements but the involved complex geometries require adjustable parameters and extensive modelling, which result in large and poorly controlled experimental uncertainties.…”
mentioning
confidence: 99%
“…Experimental data in the literature show striking similarities over a wide range of materials, including exponential dependence of low frequency conductivity on N À1/3 [1,2]. Low frequency dielectric data showing rapid increases of magnitude with decreasing frequency have been widely reported for hydrophilic solids [3][4][5][6][7][8][9][10][11][12][13][14][15] and for humidified surfaces [16,17]. Many of these data show linearity in log-log graphs and, where reported, a constant phase angle over many decades of frequency.…”
Section: Introductionmentioning
confidence: 80%
“…Values of b close to 1 are commonly found in hydrophilic solids [5,9,12,13,15] implying that the energetic disorder of the charge carrier states is small [38]. Note that b decreases with decreasing moisture content suggesting greater disorder at low moisture contents.…”
Section: Frequency Dependencementioning
confidence: 90%
“…PTFE 10 µm thin film, and placed between the metallic plates of the sample holder which is 7 maintained under a continuous dry N 2 flow. Prior to DRS measurements, the pellet is treated insitu at 220ºC for 18 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was shown that DRS is also very sensitive to the presence of guest molecules adsorbed in the nanoporosity where EFC sit [3][4][5][6][7]. This is particularly true when the adsorbed molecule is small and polar, e.g.…”
Section: Introductionmentioning
confidence: 99%